2019
DOI: 10.3390/ijgi8110514
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of GPS-Based Buffer Size on the Association between Travel Modes and Environmental Contexts

Abstract: To investigate the association between physical activity (including active travel modes) and environmental factors, much research has estimated contextual influences based on zones or areas delineated with buffer analysis. However, few studies to date have examined the effects of different buffer sizes on estimates of individuals’ dynamic exposures along their daily trips recorded as GPS trajectories. Thus, using a 7-day GPS dataset collected in the Chicago Regional Household Travel Inventory (CRHTI) Survey, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 55 publications
0
11
0
Order By: Relevance
“…At high densities, due to the fact that the density was sufficiently high, even though the metro network coverage was dense enough, it did not affect the mode of travel of the elderly, and the bus was more convenient than the metro, and it was only a short walk to the entertainment venues. The results of this study were currently different ( 44 ).…”
Section: Discussionmentioning
confidence: 83%
“…At high densities, due to the fact that the density was sufficiently high, even though the metro network coverage was dense enough, it did not affect the mode of travel of the elderly, and the bus was more convenient than the metro, and it was only a short walk to the entertainment venues. The results of this study were currently different ( 44 ).…”
Section: Discussionmentioning
confidence: 83%
“…All valid-wear GPS points for the entire participant’s wear time were used to create a time-weighted activity space using the Kernel Density Equation (KDE) model in ArcGIS with a 200 m bandwidth, which has been shown in a previous study to be a reliable distance for exposure estimation ( Lee and Kwan, 2019 ). To account for variation in amount of time participants wore devices, we normalized the time-weighted density measure values for each participant on a scale of 0–1 where the greatest amount of time spent by a participant in a location was equal to 1, and the least equal to 0 ( Jankowska et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…Specifically, 200 m GPS‐based circular buffers are created around each GPS point to calculate the features. In a recent study, 200 m was found to be the most appropriate distance for examining the associations between ATMs and environmental contexts (including trees, parks and open spaces, transit availability (Chicago Metropolitan Agency for Planning (CMAP) Data Hub, 2017), crime, and traffic accidents), obtaining the largest number of higher significance levels in environmental variables when compared to other shorter buffer distances (Lee & Kwan, 2019). As shown in Table 1, 35 predictors related to the physical, social, and safety‐related environments that drew attention from researchers in past studies were used for the accurate prediction of ATMs in likelihood mapping.…”
Section: Methodsmentioning
confidence: 99%
“…To obtain the travel modes of the trips made by the participants, we modified the classification algorithm developed by Lee and Kwan (2018). The adopted classification algorithm can automatically classify walking, biking, in‐vehicle, and running modes using GPS data as training data, achieving high predictive accuracy (97% overall) (Lee & Kwan, 2019).…”
Section: Methodsmentioning
confidence: 99%